2021
DOI: 10.4103/jehp.jehp_603_20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between health literacy in substance use and alcohol consumption and tobacco use among adolescents, Northeast Thailand

Abstract: BACKGROUND: Health literacy (HL) is an important role-play in health risk behaviors such as alcohol drinking and smoking. Inadequate HL in substance use (HLSU) is a barrier to reduce the risk of alcohol and tobacco use. This study aims to investigate the association of HLSU with alcohol consumption and tobacco use among Thai adolescents. Hence, the strengthening of HL program intervention may applied to reduce substance abuse among Thai adolescents. MATERIALS AND M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This study showed that medical students with low HL were more likely to drink alcohol, and the results of this study are consistent with those of Yangyuen et al 5 who reported that adolescents with inadequate HL are more likely to consume alcohol. One explanation is that this phenomenon occurs due to the considerable academic and employment pressures that medical students are currently facing and the tedium of medical knowledge that makes them willing to choose easy access to alcohol for a brief period of pleasure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study showed that medical students with low HL were more likely to drink alcohol, and the results of this study are consistent with those of Yangyuen et al 5 who reported that adolescents with inadequate HL are more likely to consume alcohol. One explanation is that this phenomenon occurs due to the considerable academic and employment pressures that medical students are currently facing and the tedium of medical knowledge that makes them willing to choose easy access to alcohol for a brief period of pleasure.…”
Section: Discussionsupporting
confidence: 92%
“…In 2012, the rate of alcohol use among adolescents was 21.8%, increasing to 41.2% in 2016 2 and 48.09% in 2022. 3 Previous studies have shown that the main risk factors associated with alcohol use among young people include smoking, 4 monthly household income, 5 , 6 , 7 family environment, 8 , 9 intimate partners 9 , access to alcohol, 10 , 11 alcohol expectations, 12 , 13 social norms of alcohol 14 - 16 and health literacy (HL). 17 , 18 In addition, due to inadequate HL, individuals have limited ability to access, understand, interpret, and evaluate drug-related information and low self-management knowledge to make appropriate decisions to prevent or avoid the risk of drinking or to abstain from drinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the general population of Thailand, drinking persisted even during the COVID-19 pandemic (Wichaidit et al, 2021), particularly among men (Wichaidit et al, 2019). Similarly, although drinking has declined in recent years among adolescents and youths (Assanangkornchai et al, 2020), the prevalence has remained very high in population sub-groups (Wichaidit et al, 2023) and nearly half of the participants in a recent study had inadequate levels of health literacy with regard to alcohol (Yangyuen et al, 2021). Strategies of the NAAP-II to address these gaps include providing continued support for health education, health promotion, and initiating projects to install values in abstaining from alcohol and creating opportunities to abstain from drinking (Chinanonvej, 2020; Office of the National Alcoholic Beverage Control Committee, 2022).…”
Section: Policy Area 7: Providing Information and Educationmentioning
confidence: 99%
“…[ 15 ]Adolescents also engage in self-harm and suicidal behaviors, and it is more likely to be seen in individuals who use psychoactive substances and with symptoms of conduct problems. [ 16 17 18 ] Sexual misconduct was also frequently seen in these individuals who use alcohol and tobacco. These risky behaviors of adolescents are associated with higher anterior cingulate cortex neural sensitivity, and they are particularly vulnerable to risky peer influence.…”
Section: Introductionmentioning
confidence: 99%